Machine Learning-Mediated Analysis of Physical Literacy in Children¿s Subjective Well-Being: Evidence from a Multinational Survey - de Souza-Lima, Josivaldo; Ortiz-Marholz, Paula; Ferrari, Gerson; Parra-Saldias, Maribel; Duclos-Bastias, Daniel; Godoy-Cumillaf, Andrés; Merellano-Navarro, Eugenio; Bruneau-Chávez, José; Peris-Delcampo, David; Farias-Valenzuela, Claudio; Valdivia-Mora, Pedro (MDPI, 2025)
Background/Objectives: Subjective well-being (SWB) in children is a key indicator of healthy development, influenced by physical activity and sports, with physical literacy (PL) as a potential mediator. Traditional linear models overlook non-linear and heterogeneous ef fects in diverse populations. This study uses causal machine learning (ML) to examine PL¿s mediating role between sports participation and SWB in a multinational cohort. Methods: Data from the International Survey of Children¿s Well-Being (ISCWeB) (n = 128,184 children aged 6¿14, 35 countries) were analyzed. SWB was a composite (six items, ¿ = 0.85); PL was a proxy (three items excluding sports frequency, ¿ = 0.70); sports participation was continu ous (0¿5). Confounders were age, gender, parental listening, and school satisfaction. Causal ForestDML estimated the effects; GroupKFold and bootstrap were used for robustness; SHAP/PDP was used for interpretability. Results: Total ATE = 0.083 (95% CI [0.073, 0.094]); indirect via PL = 0.055 (CI [0.049, 0.061]); direct = 0.028 (CI [0.020, 0.038]); mediation pro portion = 0.660. Sensitivity with lean PL (2 items) was as follows: indirect = 0.045 (CI [0.040, 0.050]). For SHAP, school satisfaction was (+0.28), and parents were (+0.20) top. For PDP, there was a non-linear rise at PL 4¿6 (+1.2 units) and a plateau ~9.2. The cross-cultural mean ATE = 0.083 ± 0.01 (from within-country meta-analysis); this was stronger in older children (CATE 0.30 for 12¿14). For Rho sensitivity at 0.1, it was indirect ¿0.129; at Rho sensitivity of 0.2, it was ¿0.314 (robust to low confounding). Conclusions: The findings, grounded in SDT/PYD, support interventions targeting PL through sports to enhance SWB,addressing inactivity. Limitations are its cross-sectional nature and proxy measures; we recommend longitudinal studies